Preparation of Carbon-Supported Ternary Nanocatalysts Palladium-Vanadium-Cobalt for Alcohol Electrooxidation. (26th August 2020) - Co, Thanh Thien; Pham, Thi Thanh Thao; Pham, Thi Kieu Chinh; Diep, Thi Duyen; Huynh, Le Thanh Nguyen; Le, Viet Hai
Abstract : Carbon-supported nanocatalysts palladium-vanadium-cobalt (PdVCo) were synthesized via ethylene glycol (EG) reduction reaction and NaBH4 -assisted reduction. The electrocatalytic performance for alcohol oxidation in alkaline solutions was investigated. The XRD and EDX results confirmed the incorporation of V and Co with Pd lattice to form the ternary nanocatalysts PdVCo in a single phase. The NaBH4 -assisted EG reduction process exhibited highly dispersed nanoparticles with a uniform size, and the electrochemical surface area (ECSA) determined by cyclic voltammetry in 1 M KOH was also superior. In electrocatalysis performance, the cyclic voltammetry (CV) and chronoamperometry (CA) results presented an excellent electrocatalytic activity and stability of the PdVCo-20EG-20NaBH4 sample in the alcohol electrooxidation as compared to other synthesized samples with the steady current of 52 mA/cm 2 and 21.9 mA/cm 2 in methanol and ethanol, respectively.